Change trajectory of dyadic coping and subjective well-being in patients with malignant bone tumors based on cross-lagged panel model and latent growth model: a longitudinal study - Rui Li; Chun-yan Zhang; Yue Wu; Yao Wang; Yi-fan Li; Xiao-juan Fan; Hong Song (Frontiers in Psychology)
BackgroundMalignant bone tumors can result in physical disability, which has a significant impact on the quality of patients’ survival. Additionally, patients often experience high levels of psychological distress. The subjective well-being of patients with bone tumors is low, and this low level of well-being is the direct cause of the accumulation of negative emotions and misanthropy in patients.ObjectiveThe objective of this study is to examine the developmental trajectory of dyadic coping and subjective well-being in patients with malignant bone tumors, and to investigate the predictive relationship between the two. Furthermore, this study aims to provide a theoretical basis for improving the subjective well-being of patients with malignant bone tumors.MethodsA total of 265 patients with malignant bone tumors who were hospitalized in the Department of Orthopedics of the Second Affiliated Hospital of Xuzhou Medical University in Xuzhou City, Jiangsu Province from October 2021 to April 2024 were selected as the research subjects. Their dyadic coping and subjective well-being were tracked and examined at three time points: T1 (at the time of diagnosis), T2 (1 month after diagnosis), and T3 (3 months after diagnosis). The data were analyzed using a cross-lagged model and a latent variable growth model.ResultsThe cross-lagged modeling revealed that, on average, dyadic coping levels exhibited a significant and positive predictive relationship with subjective well-being at the subsequent node. Similarly, subjective well-being levels demonstrated a significant and positive predictive relationship with dyadic coping levels at the subsequent node. The latent variable growth model demonstrated an upward trajectory in dyadic coping (S = 0.228, p = 0.047) and an upward trajectory in subjective well-being (S = 0.109, p = 0.212) in patients with malignant bone tumors from T1 to T3. Furthermore, dyadic coping exhibited a positive correlation with well-being at the initial well-being (r = 0.533, p < 0.001). Furthermore, there was a negative interaction between the rate of progression prediction and the initial level of subjective well-being (β = −0.480, p = 0.008). Additionally, the initial level of subjective well-being and the developmental rate negatively predicted each other (β = −0.749, p = 0.005). Notably, the initial level of subjective well-being was able to positively predict the developmental rate of dyadic coping (β = 0.294, p < 0.001).ConclusionThe results demonstrated a notable increase in dyadic coping and subjective well-being in patients with malignant bone tumors from the time of diagnosis to 3 months post-diagnosis. Furthermore, there was a discernible correlation between dyadic coping and subjective well-being in patients with malignant bone tumors.